Addressing the needs of children of immigrants and refugee families in contemporary ECEC settings: findings and implications from the Children Crossing Borders study. Issue 1 (2nd January 2020) - Tobin, Joseph
ABSTRACT: Children Crossing Borders was an ambitious study of the intersection of im/migration and early childhood education in five countries: England, France, Germany, Italy, and the United States. This article looks back at this study a decade later, presenting the main findings and proposing suggestions about how in the contemporary climate ECEC programs might better address the needs of the im/migrant and refugee children and families they serve. Among the key findings of the study, as already presented in the main publications of the project (Tobin, Adair, Arzubiaga, 2013. Children Crossing Borders: Immigrant Parents and Teacher Perspectives on Preschool for Children of Immigrants . New York: Russell Sage Foundation; Tobin, ed. 2016. Preschool and Im/migrants in Five Countries . Brussels: Peter Lang), are that newly arriving parents tend to be pragmatic and strategic in their ECEC preferences; practitioners are often caught between being culturally responsive to parents and following their pedagogical beliefs and principles; bicultural staff play a crucial but also underappreciated role as cultural and linguistic mediators; parents find it difficult for their voices to be heard in their children's ECEC settings; and practitioners are underprepared to deal with the challenges of working with refugees, new im/migrants, and other second language learners.